A comic based interactive digital intervention to enhance facilitation skills of nurse mentors in public facilities - results of a pilot intervention in Bihar, India - Rakesh Ghosh; Susanna R. Cohen; Nidhi Subramaniam; Seema Handu; Divya Vincent; Mikelle Lloyd; Kevin Thorn; Heidi Breeze Harris; Alisa Jenny; Dilys Walker (Taylor & Francis Group, 2023)
Background Various trainings are designed to educate nurses to become simulation educators. However, there are no good strategies to sustain their learnings and keep them engaged. We developed a series of 10 interactive digital storytelling comic episodes 'The Adventures of Super Divya (SD)' to strengthen simulation educator's facilitation knowledge, skills, confidence, and engagement. This endline evaluation presents results on the change in knowledge after watching the episodes and retention of that knowledge over 10 months. Objectives The objectives of this pilot study are to: 1) assess the change in knowledge between the baseline and post-episode surveys; and 2) understand the retention of knowledge between the post-episode and the endline survey. Methods A human-centred design was used to create the episodes grounded in the lived experience of nurse simulation educators. The heroine of the comic is Divya, a 'Super Facilitator' and her nemesis is Professor Agni who wants to derail simulation as an educational strategy inside obstetric facilities. Professor Agni's schemes represent real-life challenges; and SD uses effective facilitation and communication to overcome them. The episodes were shared with a group of nurse mentors (NM) and nurse mentor supervisors (NMS) who were trained to be champion simulation educators in their own facilities. To assess change in knowledge, we conducted a baseline, nine post-episode surveys and an endline survey between May 2021 and February 2022. Results A total 110 NM and 50 NMS watched all 10 episodes and completed all of the surveys. On average, knowledge scores increased by 7-9 percentage points after watching the episodes. Comparison of survey responses obtained between 1 and 10 months suggest that the gain in knowledge was largely retained over time. Conclusions Findings suggest that this interactive comic series was successful in a resource limited setting at engaging simulation educators and helped to maintain their facilitation knowledge over time.